PERANAN OBYEK WISATA VILLA DESAKU DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI DESA MOLOWAHU KECAMATAN TIBAWA KABUPATEN GORONTALO - Nur'ain Yunus; Harijono Imbran; Nur Eng Mokodompit (Universitas Muhammadiyah Gorontalo, 2026)
This study aims to determine the role of the Villa Desaku tourist attraction in increasing community income in Molowahu Village, Tibawa District, Gorontalo Regency. This study used a descriptive qualitative approach, using interviews with informants including the owner, several culinary vendors, visitors, and the village government. The results indicate that the Villa Desaku tourist attraction plays a significant role in increasing community income in Molowahu Village, Tibawa District, Gorontalo Regency. This role is evident in the community's income through the sale of various types of culinary delights distributed within and around the tourist attraction. This increase in income is evidenced by the community's culinary sales, which range from Rp 500,000 to Rp 2,000,000 per week. The amount of income depends on the type of culinary delights offered to visitors. The vendors' income is greatly influenced by the number of visitors each week, which can reach over 1,000. In addition to generating income, Villa Desaku provides employment opportunities for the community, including permanent recruitment and other opportunities, such as freelance work at the entrance, parking, and office boy and security guards within the Villa Desaku area.